Behçet's Disease (Adamantiades-Behçet's Disease) - Fumio Kaneko; Ari Togashi; Sanae Saito; Hideo Sakuma; Noritaka Oyama; Koichiro Nakamura; Kenji Yokota; Keiji Oguma (Clinical and Developmental Immunology)
Adamantiades-Behçet's disease (ABD) is characterized by starting with oral aphthous ulceration and developing of the systemic involvements. The pathogenesis of ABD is closely correlated with the genetic factors and the triggering factors which acquire delayed-type hypersensitivity reaction against oral streptococci mediated by IL-12 cytokine family. HLA-B51 is associated in more than 60% of the patients and its restricted CD8+ T cell response is clearly correlated with the target tissues. Bes-1 gene encoded partial S. sanguinis genome which is highly homologous with retinal protein, and 65 kD heat shock protein (Hsp-65) released from streptococci is playing an important role with human Hsp-60 in the pathogenesis of ABD. Although Hsp-65/60 has homologies with the respective T cell epitope, it stimulates peripheral blood mononuclear cells (PBMCs) from ABD patients. On the other hand, some peptides of Hsp-65 were found to reduce IL-8 and IL-12 production from PBMCs of ABD patients in active stage.